Ab initio molecular dynamics simulation of structural and elastic properties of SiO2–P2O5–Al2O3–Na2O glass. Issue 11 (1st July 2022) - Qian, Yixiao; Song, Bin; Jin, Junteng; Prayogo, Genki I.; Utimula, Keishu; Nakano, Kousuke; Maezono, Ryo; Hongo, Kenta; Zhao, Gaoling
Abstract: The effects of P2 O5 content on the structural and mechanical properties of phosphoaluminosilicate glasses were studied using ab initio molecular dynamics simulations. Structural simulations involving the partial radial distribution functions, angle distributions, and proportions of bridging oxygen and nonbridging oxygen species were performed. The results indicated that an increase in the phosphorus content disordered the distributions of the bond length and bond angle. At low phosphorus contents (P2 O5  < 5.17 mol%), phosphorus captured sodium ions in the Si–ONBO –Na linkage and formed a P–ONBO –Na linkage, completing the silicate network. With P2 O5 contents ranging from 5.17 mol% to 8.62 mol%, PO4 units existed in the glass network in the form of Si–OBO –P and Al–OBO –P linkages. At higher phosphorus contents (18.97 mol% < P2 O5  < 50.00 mol%), silicate glass network transformed into a phosphate glass network, the negative charge generated by AlO4 units was compensated by Al–OBO –P linkage. In particular, the generation mechanisms of oxygen triclusters and five‐coordinate aluminum as well as their evolutions were elaborated. Regarding the mechanical properties, atomic bonding strength was examined to analyze the intrinsic nature of the elastic modulus in phosphoaluminosilicate glass. The results indicated that P‐O bonding strength significantly contributed to the elastic modulus.